THE RELATIONSHIP BETWEEN ANXIETY AND BRUXISM IN ADULTS - Rizki Amalia; Rahmad Arifin; Galuh Dwinta Sari (Universitas Lambung Mangkurat, 2023)
ABSTRACTBackground: Anxiety disorder is a psychological condition that includes worry, anxiety, and restlessness. The prevalence of emotional anxiety disorders in Indonesia is 9.9%, anxiety can cause somatic symptoms causing irritability, muscle tension and restlessness which results in the appearance of parafunctional oral activities such as bruxism. Bruxism is a bad habit of grinding and clenching teeth excessively inadvertently which involves the activity of the masticatory muscles, resulting in clinical problems in the involved teeth, such as attrition, tooth fracture, and increased sensitivity and degree of tooth mobility, exostosis and torus of the jawbone, hypertrophy of the masticatory muscles, periodontal tissue damage, and causes headaches and temporomandibular joint damage Purpose: The purpose of the literature study was to determine the relationship between anxiety and bruxism in adults Material and Methods: All reviewed articles were obtained from searching Google Scholar, Pubmed and Science Direct data sources which have a maximum journal publication time of 10 years. Results: The review was conducted in 22 journals that were responding with the inclusion criteria such as journals available in the form of full text in Indonesian or English, the subjects of the journal were people who have an adult age suffering from anxiety and bruxism. Conclusion: there is a relation between anxiety and bruxism in adult.Keywords: Adult, Anxiety, Bruxism.